2016
DOI: 10.1101/gr.201814.115
|View full text |Cite
|
Sign up to set email alerts
|

A hot L1 retrotransposon evades somatic repression and initiates human colorectal cancer

Abstract: Although human LINE-1 (L1) elements are actively mobilized in many cancers, a role for somatic L1 retrotransposition in tumor initiation has not been conclusively demonstrated. Here, we identify a novel somatic L1 insertion in the APC tumor suppressor gene that provided us with a unique opportunity to determine whether such insertions can actually initiate colorectal cancer (CRC), and if so, how this might occur. Our data support a model whereby a hot L1 source element on Chromosome 17 of the patient's genome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

18
277
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 248 publications
(316 citation statements)
references
References 50 publications
18
277
0
3
Order By: Relevance
“…Exonic L1 insertions are highly detrimental to gene function (Kazazian et al 1988;Miki et al 1992;Scott et al 2016), and intronic insertions can compromise transcript integrity by introducing cryptic splice sites and polyadenylation signals and can interfere with RNA polymerase processivity, particularly when oriented in sense relative to the interrupted gene (Perepelitsa- Belancio and Deininger 2003;Han et al 2004;Belancio et al 2008). Furthermore, L1 insertions are occasionally associated with deletions and rearrangements to target site DNA, including extreme examples such as chromosomal translocations (Gilbert et al 2002(Gilbert et al , 2005.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Exonic L1 insertions are highly detrimental to gene function (Kazazian et al 1988;Miki et al 1992;Scott et al 2016), and intronic insertions can compromise transcript integrity by introducing cryptic splice sites and polyadenylation signals and can interfere with RNA polymerase processivity, particularly when oriented in sense relative to the interrupted gene (Perepelitsa- Belancio and Deininger 2003;Han et al 2004;Belancio et al 2008). Furthermore, L1 insertions are occasionally associated with deletions and rearrangements to target site DNA, including extreme examples such as chromosomal translocations (Gilbert et al 2002(Gilbert et al , 2005.…”
mentioning
confidence: 99%
“…In 1992, Miki et al identified an exonic L1 insertion into the APC gene that very likely led to tumor initiation in a case of colorectal cancer, providing the first direct evidence for L1 involvement in oncogenesis (Miki et al 1992). Since then, spurred by the advent of high-throughput sequencing approaches for identifying endogenous somatic L1 insertions, L1 mobilization events have been uncovered in a plethora of tumor types, including lung, ovarian, breast, colorectal, prostate, liver, pancreatic, gastric, endometrial, and esophageal cancers (Iskow et al 2010;Lee et al 2012;Solyom et al 2012;Shukla et al 2013;Helman et al 2014;Tubio et al 2014;Doucet-O'Hare et al 2015, 2016Ewing et al 2015;Paterson et al 2015;Rodic et al 2015;Scott et al 2016). Although these studies have elucidated driver L1 mutations exonic to APC and PTEN, most of the cataloged tumor-specific L1 insertions represent likely passenger events (Helman et al 2014;Scott et al 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In somatic tissues, both elevated L1 expression and retrotransposition have been strongly associated with many types of human cancers (6,7). In a few cases, specific retrotransposition events (i.e., insertions) have been determined to drive tumorigenesis (8,9). In the germline, retrotransposon insertions are responsible for sporadic cases of human genetic diseases, including hemophilia A (10) and neurofibromatosis 1 (11).…”
mentioning
confidence: 99%
“…Studies demonstrate that some cancers contain multiple somatic inserts that can be traced back to one individual "hot" element. 23,24 Another layer of complexity regarding somatic disease risk, such as cancer, derives from the evidence that TE content can also vary between different tissues due to somatic activity [25][26][27] or activity during early embryonic developmental stages. 28 Sequencing studies from a variety of cancer and matched normal tissues suggest that somatic retrotransposition occurs with varying efficiency, [29][30][31][32] which could reflect even another component contributing to more variation between individuals.…”
mentioning
confidence: 99%